Clinical outcomes differ among the different ablation technologies used for surgical atrial fibrillation therapy - Swanson, David K. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Multiple ablation technologies are used to provide atrial fibrillation therapy during cardiac surgery. A rigorous search was performed to identify all peer-reviewed papers that provided clinical outcomes data following the ablation therapy. A META analysis showed significant differences in clinical outcomes by ablation technology type: clinicians using temperature-controlled RF power delivery achieved higher rates of normal sinus rhythm at follow-up and patients ablated with microwave ablation had lower rates of normal sinus rhythm than the average of all ablation-treated patients. Permanent pacemaker implantation rates were higher than average for patients treated with microwave or argon-based Cryoablation technologies, but were lower than the average for patients treated using temperature-controlled RF.